Tax Planning: The Mediating Effect of Profitability, Return on Assets and Firm Value - Tonbraladoh, SINEBE, Michael; AKPOMIEMIE, Alex Omuerore (Research Parks Publishers, 2023)
This study investigated the role profitability, Return on Assets and Firm Value plays in the preparation of tax for businesses. The study utilized a causal research approach to investigate the cause-and-effect relationship between tax planning and the value of businesses. This study specifically aims to evaluate the effect of profitability on the firms' value and the relationship between Return on Assets and its influence on firm value. The research population consisted of 64 out of 76 listed non-financial firms on the Nigeria Stock Exchange and within the period of 2011 to 2020. Using STATA 13 to analyze data retrieved from the annual financial statements of chosen firms, we recommend that, management should examine their tax savings activities in order to enable them maintain a stable performance; and also to improve the value of the firms’ income flow from extra income generation from the reduction of expenses.